The Latin Language and Medical Terminology. Quizzes and Tasks for Practical Skills Evaluation for the First-Year Students of the Medical Faculties with the English Medium of Instruction, specialty 222 “General Medicine” - Titiyevska, T.; Gordiyenko, O.; Kulichenko, A.; Тітієвська, Тетяна Василівна; Гордієнко, Олена В'ячеславівна; Куліченко, Алла Костянтинівна (Запорізький державний медичний університет, 2019)
The manual for the first-year students of the medical faculties with the English medium of instruction contains quizzes and tasks for practical skills evaluation of the discipline “The Latin Language and Medical Terminology”, speciality 222 “General Medicine”. The aim of the manual is to assist the teachers with the organization of learning process for the first-year students with the English medium of instruction and evaluate their practical skills during each lesson and at the end of each semester.